Korelasi antara Minat Baca dengan Kemampuan Menulis Teks Prosedur Kompleks pada Siswa Kelas VII SMP Negeri Sumber Rejo Kabupaten Musi Rawas - Riyanti, Supini; Susetyo, Susetyo; Wardhana, Dian Eka Chandra (UNIB Press, 2019)
The purpose of this study was to determine whether there is a positive and significant correlation between interest in reading with the ability to write complex procedure texts in Indonesian subjects in Grade VII students of SMP Negeri Sumber Rejo, Musi Rawas Regency. The research method uses a simple correlation method. Data collection techniques using questionnaires and tests. The population in this study was 81 students, sampling from the entire population divided by the number of students multiplied by the prediction set at 10%, then obtained 45 students. Analysis of the data used is the Pearson Product Moment Test. The results showed that there was a positive and significant relationship between interest in reading with the ability to write procedural texts in Grade VII students of SMP Negeri Sumber Rejo, Musi Rawas Regency. This is evidenced by the correlation coefficient of 0.01 smaller than 0.05 at a significant level of 5%. This proves that at a significant level ? = 0.05 or at the level of confidence of 95% there is a significant relationship between interest in reading and the ability to write complex procedural texts in SMP Negeri Sumber Rejo, Musi Rawas Regency.